Strategi dan Tantangan Mewujudkan Masyarakat Islami Melalui Program KKN IAI STIBA Makassar di Desa Tamasaju: Strategies and Challenges in Realizing an Islamic Society Through the IAI STIBA Makassar Community Service Program (KKN) in Tamasaju Village - Ahmad Syaripudin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
The Community Service Program (KKN) is a form of community engagement that implements the Tridharma of Higher Education. The KKN program of IAI STIBA Makassar was conducted in Tamasaju Village, Galesong Utara District, Takalar Regency, to strengthen religious development and support the realization of an Islamic society. This article aims to describe the program strategies, identify implementation challenges, and analyze its contribution to community religious activities. A participatory approach was employed through observation, needs assessment, program planning, implementation, and evaluation. Data were collected through observations, interviews, documentation, and field notes, and analyzed using a descriptive qualitative method. The findings show that educational institution-based religious development, collaboration with village authorities and community leaders, the DIROSA program, PELITA activities, and the distribution of Qur’ans and learning halaqahs increased community participation in religious activities. Major challenges included limited implementation time, varying participant abilities, and the need for sustainable post-program religious development.